2012
DOI: 10.1021/cb200474a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probes for Imaging Endogenous β-Actin mRNA in Living Cells Using Fluorescent Protein-Tagged Pumilio

Abstract: Subcellular localization and dynamics of mRNAs control various physiological functions in living cells. A novel technique for visualizing endogenous mRNAs in living cells is necessary for investigation of the spatiotemporal movement of mRNAs. A pumilio homology domain of human pumilio 1 (PUM-HD) is a useful RNA binding protein as a tool for mRNA recognition because the domain can be modified to bind a specific 8-base sequence of target mRNA. In this study, we designed PUM-HD to match the sequence of β-actin mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…This assay is sometimes seen as qualitative, because it does not indicate actual binding affinities, but it has proven useful in the study of RNA-binding proteins such as Pumilio because it allows for such interactions to be measured at a functional level in living cells (23)(24)(25)(26). In particular, split fluorescent protein reconstitution was used to test on-target binding of three different Pum variants to NRE variants, and also previously used to visualize binding of PumHD variants to the mRNAs for human β-actin and NADH dehydrogenase subunit 6 (23)(24)(25)(26). Based upon earlier literature,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assay is sometimes seen as qualitative, because it does not indicate actual binding affinities, but it has proven useful in the study of RNA-binding proteins such as Pumilio because it allows for such interactions to be measured at a functional level in living cells (23)(24)(25)(26). In particular, split fluorescent protein reconstitution was used to test on-target binding of three different Pum variants to NRE variants, and also previously used to visualize binding of PumHD variants to the mRNAs for human β-actin and NADH dehydrogenase subunit 6 (23)(24)(25)(26). Based upon earlier literature,…”
Section: Resultsmentioning
confidence: 99%
“…Previous works had demonstrated, using proteins that bind to specific RNA sequences, the measurement of mRNA expression level (23,24), imaging of mRNA dynamics (23)(24)(25)(26)32), and enhancement and suppression of mRNA translation (6,30,31,33) with variants of natural RNA-binding proteins. We demonstrated that our Pumby architecture, which uses a single repeated module to support protein generation (analogous to the TALE design), enables performance equivalent to the original Pumilio protein.…”
Section: Discussionmentioning
confidence: 99%
“…Pumilio-based RNA imaging has enabled subcellular detection of the mRNAs of mitochondrial NADH dehydrogenase and -actin, as well as retroviral RNA in mammalian cultured cells (20)(21)(22)(23), and of the genomes of Tobacco mosaic virus, Potato virus X and Turnip mosaic virus in live plant tissue (24)(25)(26)(27). Of particular relevance to the topic of this volume, Pumilio-based RNA imaging has recently shown that Potato virus X is present in membrane structures at the entrances of plasmodesmata that also contain the viral replicase (27).…”
Section: Rna-binding Domain Of Pumilio Proteinsmentioning
confidence: 99%
“…However, a fusion with the FP inserted between the PUMHDs (NLS-PUMHD-FP-PUMHD) was recently used in mammalian cells (23) and may also work in plants.…”
Section: Choice Of Reporter Systemmentioning
confidence: 99%
See 1 more Smart Citation